Aligned Single‐Crystalline Perovskite Microwire Arrays for High‐Performance Flexible Image Sensors with Long‐Term Stability. Issue 11 (18th January 2016) - Deng, Wei; Zhang, Xiujuan; Huang, Liming; Xu, Xiuzhen; Wang, Liang; Wang, Jincheng; Shang, Qixun; Lee, Shuit‐Tong; Jie, Jiansheng
Abstract : A simple, low‐cost blade‐coating method is developed for the large‐area fabrication of single‐crystalline aligned CH3 NH3 PbI3 microwire (MW) arrays. The solution‐coating method is applicable to flexible substrates, enabling the fabrication of MW‐array‐based photodetectors with excellent long‐term stability, flexibility, and bending durability. Integrated devices from such photodetectors demonstrate high performance for high‐resolution, flexible image sensors.